The ethical significance of user-control in AI-driven speech-BCIs: a narrative review - van Stuijvenberg, O. C.; Samlal, D. P. S.; Vansteensel, M. J.; Broekman, M. L. D.; Jongsma, K. R. (Frontiers in Human Neuroscience, 2024)
AI-driven brain-computer-interfaces aimed at restoring speech for individuals living with locked-in-syndrome are paired with ethical implications for user’s autonomy, privacy and responsibility. Embedding options for sufficient levels of user-control in speech-BCI design has been proposed to mitigate these ethical challenges. However, how user-control in speech-BCIs is conceptualized and how it relates to these ethical challenges is underdetermined. In this narrative literature review, we aim to clarify and explicate the notion of user-control in speech-BCIs, to better understand in what way user-control could operationalize user’s autonomy, privacy and responsibility and explore how such suggestions for increasing user-control can be translated to recommendations for the design or use of speech-BCIs. We identified three themes. First, we identified types of user control, including executory control that can protect voluntariness of speech, and guidance control that can contribute to semantic accuracy. Second, we identified potential causes for a loss of user-control, including contributions of predictive language models, a lack of ability for neural control, or signal interference. Such a loss of user control may have implications for semantic accuracy and mental privacy. Third we explored ways to design for user-control. While initiation signals for users may increase executory control, they may conflict with other aims such as speed and continuity of speech. While design mechanisms for guidance control remain largely conceptual, similar trade-offs in design may be expected. We argue that preceding these trade-offs, the overarching aim of speech-BCIs needs to be defined, requiring input from current and potential users. Additionally, conceptual clarification of user-control and other (ethical) concepts in this debate has practical relevance for BCI researchers. For instance, different concepts of inner speech may have distinct ethical implications. Increased clarity of such concepts can improve anticipation of ethical implications of speech-BCIs and may help to steer design decisions.